PENGARUH RETURN ON ASSET DAN EARNING PER SHARE TERHADAP DIVIDEND PAYOUT RATIO YANG TERDAFTAR DI BURSA EFEK INDONESIA - Annisa, Annisa; Yusran, Rio Rahmat (SCIENTIA JOURNAL, 2019)
The purpose of this study to determine the effect of return on assets and earnings per share against dividend payout ratio listed on the stock exchange Indonesia. Independent variables used are Return On Assets and Earning Per Share. Dependent variable used is Dividend Payout Ratio. The population in this research is the data of Return On Assets, Earning Per Share, and Dividend Payout Ratio at LQ45 Company listed on Indonesia Stock Exchange for 5 years from 2013-2017. The sample in this research is LQ45 company which listed in Indonesia Stock Exchange Exchange (IDX). Data analysis techniques in this study include multiple linear regression. Test results in this study indicate that the variable Return On Asset has a significant effect on Dividend Payout Ratio. From the test results of the above variables, Return On Asset shows the value of t count 2.493> ttable value 2.016 with the significance number 0.017 <0.05. Earning Per Share variable has no effect on Dividend Payout Ratio. From the test results of the above variables, Earning Per Share shows that the value of tcount of 1.420 <ttable value of 2.016 with a signification number of 0.163> 0.05. Together Return On Assets and Earning Per Share together significant effect on Dividend Payout Ratio with significant numbers of 0.006 <0.05 and Fcount> Ftable, where the value Fcount 5.895> Ftable of 3.21.